1982
DOI: 10.1083/jcb.94.2.335
|View full text |Cite
|
Sign up to set email alerts
|

Anti-immunoglobulin, cytoplasmic free calcium, and capping in B lymphocytes.

Abstract: This paper examines, in mouse spleen lymphocytes, the effect of anti-immunoglobulin (anti-Is) on the cytoplasmic free calcium concentration, Capping of surface Ig represents a dramatic reorganization of membrane components apparently involving cytoskeletal elements and requiring metabolic energy (2, 12). Formation of caps is followed by contractile activity and cell motility. Rather little is known of how ligand binding stimulates these processes although changes in ion flux and potential difference across the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
48
1

Year Published

1984
1984
2013
2013

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 208 publications
(54 citation statements)
references
References 14 publications
5
48
1
Order By: Relevance
“…Previous studies demonstrated that when the loading is performed in Ca='-containing media, the cell is able to compensate for the generation of the high-affinity Ca 2+ chelator by increasing the total cytoplasmic calcium, so that [Ca 2 +]i remains unchanged (22,30,40,41) . We previously showed that the release response brought about in quint-loaded PC 12 cells by high K+ and a-latrotoxin was not significantly different from that in control cells (22) .…”
Section: Quint-loaded Cellsmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous studies demonstrated that when the loading is performed in Ca='-containing media, the cell is able to compensate for the generation of the high-affinity Ca 2+ chelator by increasing the total cytoplasmic calcium, so that [Ca 2 +]i remains unchanged (22,30,40,41) . We previously showed that the release response brought about in quint-loaded PC 12 cells by high K+ and a-latrotoxin was not significantly different from that in control cells (22) .…”
Section: Quint-loaded Cellsmentioning
confidence: 99%
“…Quint can be used not only to measure [Ca 2+]i but also to control and modify this parameter . In particular, when the loading is performed in Ca 2 '-free media, homeostasis is not maintained and [Ca 2 +] ; is decreased to very low levels (30) . In 63 0 THE JOURNAL of CELL 131OLOGY -VOLUME 99, 11 184 …”
Section: Quint-loaded Cellsmentioning
confidence: 99%
See 2 more Smart Citations
“…One of the earliest responses associated with crosslinking of slg is an increase in the level of cytoplasmic free calcium ([Ca2+]j). This was initially inferred from measurements of 45Ca2" distribution (2) and later confirmed by direct determinations of [Ca2+], using fluorescent probes such as quin2 (3). At least part of the Ca2" that appears in the cytoplasm originates from intracellular stores, inasmuch as anti-slg can elevate [Ca2+], in cells suspended in Ca2+-free media containing EGTA (3,4).…”
Section: Introductionmentioning
confidence: 99%